Understanding the Cultural Reality of Shinobi through the Anime Series of Naruto & Naruto Shippūden - Gema Budiarto (IZUMI, 2023)
Naruto and Naruto Shippūden are the anime series adapted from Masashi Kishimoto’s manga. The Naruto series aired in Japan from 2002-2007, while Naruto Shippūden was from 2007-2017. These animes are interconnected, Naruto is part one and Naruto Shippūden is part two. These animes took some of the original traditions of the Shinobi though not the same. Indeed, Shinobi is real and not a myth. If studied historically, Shinobi were considered ancient warriors of Japan other than the Samurai-侍. Nevertheless, the theory about the birth of the Shinobi is complicated to trace, but Shinobi existed in feudal Japan, especially during the Sengoku Jidai-戦国時代. This research tries to examine the cultural reality and facts of the Shinobi in the Naruto and Naruto Shippūden series. The method used in this research is descriptive qualitative. The result of this study shows that Naruto and Naruto Shippūden adopted the reality of the Japanese Shinobi. Some of the original Shinobi elements were adopted in this anime such as the use of weapons, hand seals, the use of nature elements, and so on. Through these animes, viewers are invited to recognize the traditions of the Japanese Ninja world. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor